At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

f '(x)=4x^3+6x did you get this far?

ok i know how you got there

f '(1)=4+6=10

10 is the slope of the tangent line at x=-1

let me do it on paper one sec

oh i plug in 1

You didn't plug in -1

right polpak

f '(-1)=-10 not 10

y=-10x+b we need to know b
we know a point on this line

Nah, just find the slope of the tangent and plug in that slope into point slope formula

Ok after you get the slope of the tangent what did you plug in to get you (x,y) values?

If x=1, then y=....

damn stupid 1

-1

\(x = -1 \implies f = x^4+3x^2 = ?\)

lol

thats 4 but we are stillnot jiving with the stupid books answer

we are fixing to

so we have y=-10x+b
4=-10(-1)+b

Take the slope (-10) and the point (-1,4) and plug into point slope.
\(y-y_0 = m(x-x_0)\)

solve for b

you can use either way

Where m is the slope, \(x_0,y_0\) are the x and y for your point.

b=4-10=-6
so y=-10x-6

i like slope intercept its more fun to me for some reason

Ok where did we pull the y value from (4) sorry i missed how we came up with that one

Plug in x=-1 to the original equation for f(x)